Guru dalam Perpektif Islam - Khaerunnisa K; Syamsuddin S (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the role and position of teachers from the perspective of Islamic law. It is a literature-based study that relies primarily on library sources as its main data. The analytical method employed follows the framework of library research using a qualitative descriptive approach. The findings indicate that the concept of a teacher in the Islamic perspective has a broad and profound meaning. A teacher is not merely a transmitter of knowledge but also an educator responsible for shaping students’ character, morals, and spirituality. Teachers are understood as professionals whose duties include educating, guiding, directing, and developing the full potential of learners in a holistic manner, encompassing cognitive, affective, and psychomotor aspects. In the context of Islamic education, the term “teacher” encompasses various dimensions, such as murabbi (nurturer), mu’allim (instructor), mu’addib (cultivator of good manners and ethics), mudarris (teacher), mursyid (guide), and muzakki (purifier), each reflecting a comprehensive role in the educational process, ranging from the transmission of knowledge to the development of moral character and spirituality.